Laundry Express / Ahmad Akif Farhan Mohd Yuzi ... [et al.] - Mohd Yuzi, Ahmad Akif Farhan; Jaafar, Muhammad Fathullah Hakim; Azman, Muhammad Afiq; Khamarazaman, Amer Fikri; Mohd Azizi, Mohamad Aizat Hilmi (2021)
Laundry express is a self-service laundry that provides services such as washing, drying and folding. Laundry Express will be opened 24 hours a day to record a maximum profits as we can. We also do have an online reservation as well as delivery service for our customers who do not have time to wait in the laundry place. We will have our own delivery staff who will be responsible for the picking of dirty clothes as well as delivery of clean clothes each house will be assigned with codes which will make the person easy to identify this will avoid misplacement as well as ensure proper safety of clothes. These services is dedicated to consistently providing high customer satisfaction by using reliable machines and furnishing a clean, enjoyable atmosphere at an affordable price and value relationship. Our mission is to provide best in class laundry room operations to our customers by delivering superior quality and service. Laundry Express would like to set itself apart from other laundromats that may offer only one or two services. Although the focus of Laundry Express is a washing and drying service, we do wish to offer our clients the convenience of these other services in one location. Those services include folding and potentially pick-up or delivery service, as well as online reservation and membership for pick-up and delivery. Most importantly, it is our convenience that sets us apart from the competition. It has been shown that the best method of advertising is through word-of-mouth. No major newspaper ad campaign is planned. However, we shall run weekly specials. In addition, we shall have an incentive program for referrals. Those customers who refer someone else to the store will be rewarded with two free washes, and the referee will receive an introductory gift of a free wash. In addition, we will ensure a clean environment, reliable machines, and friendly, prompt services. Our business is a start up business, hence it is our responsibility to have a clean facility that strives to ensure a complete customer satisfaction in overall. Laundry Express will be set up to provide a conducive environment by providing a free Wi-Fi. This will be accomplished by having ample long bench chairs for customers to use as a place to rest and can surf the social media on their smartphone while they are doing their laundry. Laundry Express will also offer a vending machine to encourage people to stay for longer time and spend more money. Customers can buy their drinks or snacks from the vending machine so that they do not have to go out from the laundry just to buy a drinks or snacks at nearer shop. Our Laundry Express provide convenience ventilation system too. At waiting room, there were several air conditioner, fans and windows provided. It makes the waiting room cool and comfortable. Other than that, exhaust fans also included which to draw hot air out of building and thereby cause equal ventilation flow into the building. Since our mission is to provide the highest quality laundry room operations to our customers by delivering superior quality and service, our services will exceed the expectations of the customers. In order to achieve the mission and vision of Laundry Express, we make a business plan to illustrate business planning to start a business by seeking a loan. The timing was just right for us to start this new venture as the demand of laundry service nowadays keep increasing and has made it as one of business opportunity with a great income potential.